2021
DOI: 10.1177/02662426211061679
|View full text |Cite
|
Sign up to set email alerts
|

Crisis and arbitrage opportunities: The role of causation, effectuation and entrepreneurial learning

Abstract: This article examines the process by which entrepreneurs identify and work with an arbitrage opportunity emerging from an episodic crisis. Although prior research has investigated the role of entrepreneurial characteristics and context on opportunity development, the specific manner in which these factors emerge in the course of opportunity development during a crisis remain underexplored. By adopting a qualitative approach grounded in case studies of eight entrepreneurs in the US distillery industry, this art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 118 publications
(186 reference statements)
0
6
0
Order By: Relevance
“…Sarasvathy (Sarasvathy, 2008) reinforces the importance of experiential knowledge, highlighting that "Sustained performance over long periods of time requires that experts outlive failures, cumulate successes, and learn from both" (p.20). Another one (Khurana et al, 2022) found evidence of combinations of both logics but in alternating magnitutes, with a higher proportion of causation first and of effectuation later in the specific context of opportunity exploitation.…”
Section: Alternating Between the Two Logics: A Life Cycle Issue (Meso...mentioning
confidence: 98%
See 1 more Smart Citation
“…Sarasvathy (Sarasvathy, 2008) reinforces the importance of experiential knowledge, highlighting that "Sustained performance over long periods of time requires that experts outlive failures, cumulate successes, and learn from both" (p.20). Another one (Khurana et al, 2022) found evidence of combinations of both logics but in alternating magnitutes, with a higher proportion of causation first and of effectuation later in the specific context of opportunity exploitation.…”
Section: Alternating Between the Two Logics: A Life Cycle Issue (Meso...mentioning
confidence: 98%
“…As in the case of Khurana et al (2022), the use of combined logics is usually a macro level decision, in other words, when context is complex and variable, requiring the decision logic to follow. It is not necessarily dependent on the entrepreneur/decision maker or on the age/life cycle of the enterprise, the decision logic depends on the situation/decision at hand, needing to be analyzed and decided on a case-by-case basis (Fisher, 2012;Kaufmann, 2013;Crick & Crick, 2014;Sitoh et al, 2014;Nummela et al, 2014;Dutta et al, 2015;Maine et al, 2015).…”
Section: Combining Both Logics: a Macro Level Issue Or A Matter Of Jo...mentioning
confidence: 99%
“…The way entrepreneurs learn is diverse, for example, from peers, experience and consumers and suppliers, etc. (Hunter and Lean, 2018; Khurana et al , 2022). Essentially, all of these processes are linked to the informational or interactive ways of learning, being primarily dependent on the entrepreneurs’ own experience.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are demands which are not formally stated but it is hoped that MSMEs become the "heroes" who turn on the economic foundation of a country, especially during the hard times of the Covid-19 pandemic (Maritz et al, 2020). The research done by Khurana et al (2022), stated that during the Covid-19 crisis, the companies studied identified arbitrage opportunities and then tried to make them happen using the effectuation approach (owned resources). The decision to identify arbitrage opportunities and make them happen is a temporary decision to bridge the company's need to survive in difficult times.…”
Section: Introductionmentioning
confidence: 99%